Tuning Cobalt and Nitrogen Co‐Doped Carbon to Maximize Catalytic Sites on a Superabsorbent Resin for Efficient Oxygen Reduction. Issue 20 (24th September 2018) - Liu, Mengran; Lin, Hai; Mei, Zongwei; Yang, Jinlong; Lin, Jie; Liu, Yidong; Pan, Feng
Abstract: The electrocatalytic performance and cost of oxygen reduction reaction (ORR) catalysts are crucial to many renewable energy conversion and storage systems/devices. Recently, transition‐metal/nitrogen‐doping carbon catalysts (M–N–C) have attracted tremendous attention due to their low cost and excellent catalytic activities; however, they are restricted in large‐scale commercial applications by complex preparation processing. Here, a facile strategy to prepare Co–N–C catalysts has been developed. A kind of superabsorbent resin normally found in diapers, poly(acrylic acid‐acrylamide), is used to adsorb a transition‐metal cobalt salt and a pyrolysis strategy at 800 °C under an argon atmosphere is followed. The resin simultaneously plays a multiple role, which includes structural support, dispersing cobalt ions by coordinate bonds, and providing a carbon and nitrogen source. Attributed to the conductive carbon frameworks and abundant catalytic sites, the Co–N–C catalyst exhibits an excellent electrocatalytic performance. High onset potential (0.96 V vs. reversible hydrogen electrode, RHE), half‐wave potential (0.80 V vs. RHE), and a large diffusion‐limited current density (4.65 mA cm −2 ) are achieved for the ORR, which are comparable or superior to the commercial 20 % Pt/C and reported M–N–C ORR electrocatalysts. This work provides a universal dispersion technology for Co–N–C catalyst, which makes it a very promising candidate toward the ORR. Abstract : Superabsorber turned into a catalyst : Dispersing technology that uses a superabsorbent resin to adsorb metal ions followed by a pyrolysis strategy to fabricate a Co–N–C catalyst for the oxygen reduction reaction has been described. The resin provides a framework and a doping element source to form actives sites. The catalyst exhibits an excellent electrocatalytic performance with low cost.